Investigating the Relationship between Automatic Negative Thoughts and Experiential Avoidance with Psychological Distress and the Mediating Role of Cognitive Emotion Regulation in Patients with a History of Suicide Attempt - Ahmad Alipour; Afsaneh Rahimi; Shahin Shadnia; Mitra Rahimi; Peyman Erfan Talab Evini; Sayed Masoud Hosseini; Babak Mostafazadeh (Iranian Journal of Psychiatry)
Objective: Automatic negative thoughts have an important role in development of a persistent negative cognitive bias, which may ultimately result in suicidal ideation. The primary objective of the present study was to examine the relationship between automatic negative thoughts and experiential avoidance in relation to psychological distress. Method: The study sample comprised 441 individuals who had attempted suicide. Participants underwent interviews utilizing standardized questionnaires including Automatic Thoughts Questionnaire, Kessler Psychological Distress Scale, Acceptance and Action Questionnaire–II, and Cognitive Emotion Regulation Questionnaire along with its nine subscales. After internal relationships assessment among the research variables, outlier detection was done using the boxplot analysis and standard deviation distance metrics. To analyze the direct and indirect associations between the input and output variables, Structural Equation Modeling (SEM) was employed. In addition, SPSS-28 and Amos 29 software were used to analyzed the data. Results: The final model showed that automatic negative thoughts were significantly inversely associated with adaptive cognitive emotion regulation (β = -0.42, P ≤ 0.01) and significantly positively related to both maladaptive cognitive emotion regulation (β = 0.49, P ≤ 0.01) and psychological distress (β = 0.53, P < 0.01). Additionally, experiential avoidance showed a significant positive relationship with maladaptive cognitive emotion regulation (β = 0.22, P < 0.01). Conclusion: This research demonstrated that automatic negative thoughts could worsen psychological distress through the regulation of cognitive emotion in those who had a history of suicide. By the clinical management of automatic negative thoughts and shifting individuals’ cognitive emotion regulation toward adaptive strategies, there is potential for a substantial reduction in suicidal ideation and attempts which can be evaluated in future clinical trials.